Does Tourism Induce Sustainable Human Capital Development in BRICS Through the Channel of Capital Formation and Financial Development? Evidence From Augmented ARDL With Structural Break and Fourier-TY Causality - Li, Jun; Qamruzzaman, Md. (Frontiers in Psychology, 2022)
motivation of the study is to explore the role of tourism in the process of sustainable human capital development in BRICS for the period 1984-2019. the study applied several econometrical techniques for exposing the empirical association such as variables order of integration has revealed by implementing both conventional and structural break unit root test, the long-run cointegration has examined by employing combined cointegration test, long-run and short-run coefficients was detected through implementing the Augmented Autoregressive Distributed Lagged (AARDL), and directional causality following Toda-Yamamoto with Fourier function. The result of the unit-roots test established variables is integrated in mixed order; variables are stationary either at a level or after the first difference. The estimated test statistics from the combined cointegration test and AARDL confirmed the long-run association between tourism, gross capital formation, financial development, and human capital development. In the long run, tourism revealed a positive and statistically significant tie with human capital development; moreover, the joint effects that are interactive terms between TOR*GCF and TOR*FD established a positive and statistically significant relationship with human capital development. In addition, the causality test revealed the feedback hypothesis available between tourism and human capital development in all sample countries except India. On conclusion note, the role of tourism development is critically important for sustainable human capital development in BRICS; therefore, in case of a policy-making concern, it is inevitable to address the tourism issues with care for capitalizing on the benefits for tourism development.